Strategy for Developing Android-Based Teaching Materials for Text-based Indonesian Learning as an Implementation of the Independent Curriculum in Junior High School - Ramdhani, Intan Sari; Muhyidin, Asep; Hidayat, Sholeh (PPSDP International Journal of Education, 2023)
This study aims to determine strategies for developing android-based teaching materials for text-based Indonesian language learning as an implementation of the independent curriculum in junior high schools. Based on the achievements of learning Indonesian in the independent curriculum, the various texts studied constitute a line of thought that can optimize the use of language for work and lifelong learning. This research method is literature study, namely the method of collecting data by understanding and studying theories from various literature related to research. Therefore, the research data is in the form of data that is relevant to the topic. The data comes from books and research articles that have been published in national and international journals. The strategy in developing android-based teaching materials for text-based Indonesian learning can be carried out by applying the ADDIE development model to produce teaching material prototypes in the form of applications that contain multimedia content by combining several learning media such as text, audio, graphics, images, and video to improve the quality of learning Indonesian and increase student learning independence.